Evaluation of winter cereals for double purpose - Fontaneli, Renato Serena; Fontaneli, Roberto Serena; Silva, Genaldo da; Koehler, David (Pesquisa Agropecuaria Brasileira, 1996)
Sixteen winter cereal genotypes (oats, rye, triticale, and barley) were evaluated for forage and grain yield at the experimental area of the School of Agronomy, Passo Fundo, state of Rio Grande do Sul, southern Brazil, in 1992. Three cutting frequencies were applied: no cutting, one and two cuttings. A randomized block design with split-plots and three replicates were used. The crops were established under conventional tillage. The fertilization was 300 kg1ha of 5-25-25, plus 22.5 kg/ha of N 45 days after emergence, and 22.5 kg/ha of N after the first and second cuttings. Winter cereals were sown on May 5, 1992, by hand, with 100 seeds/m in lines spaced 0.2 m apart. The winter cereals herbage was harvested when plants were 30 cm high. Dry matter (DM) yield, grain yield, crude protein yield, and crude protein content (PB%) were determined. The rye BR-1 showed the best performance for forage and crude protein yield, whereas oat UPF- 15 was outstanding for grain yield. In addition, triticale BR-4 and oats UPF-13, UPF-14, CTC-2, and UFRGS-12 were promising for double purpose.